Analisis Kepuasan Mahasiswa Terhadap Perkuliahan Online - Sri Pujilestari; Sri Harini; Nailul Munah (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
This study aims to determine the level of student satisfaction with online lectures during the Covid-19 pandemic which is still ongoing today. Variables measuring student satisfaction with online lectures are limited to aspects of learning including lecture facilities, learning media, and the implementation of online lectures. This research method uses descriptive analysis techniques. Data was collected using a questionnaire, then the data was analyzed using statistical tests to determine the validity and reliability of the instrument, multicollinearity test, and ordinal logistic regression analysis and regression parameter tests at the 95% confidence level. Based on the test results the instrument is declared valid and reliable, and the obtained regression model is feasible to use. The results of the interpretation of the model lead to conclusions, (a) the probability of students who are satisfied with online lectures in the aspect of lecture facilities is 2.21 times compared to students who are not satisfied; (b) the probability of students being satisfied with online lectures in the aspect of learning media is 1.53 times compared to students who are dissatisfied; and (c) the probability of students being satisfied with online lectures in the aspect of lecture implementation is 2.28 times compared to students who are not satisfied.